Balanced scorecard: a proposal for strategic management of a rural cooperative credit - Kruger, Silvana Dalmutt; Simionato, Aline; Zanella, Cleunice; Petri, Sérgio Murilo (Revista de Administração da UFSM, 2018)
This study proposes a model for organizational strategic management of a credit union, through the use of the Balanced Scorecard (BSC) and the perspectives proposed by Kaplan and Norton (1997), to identify what are the benefits that the implementation of the BSC can offer for a credit union. Characterized as an exploratory case study applied to a credit union in the state of Santa Catarina, with analysis of qualitative data. For structuring the proposal considered the responses of managers and employees and the four perspectives proposed by the BSC, pondering goals, objectives and initiatives for financial prospects, customers, internal processes and learning and growth. The study results show that: (i) the weaknesses of the institution can be corrected based on goals and initiatives especially from the standpoint of customers and improve internal processes; (ii) identification of goals and objectives allows the definition of initiatives directly focused on achieving better outcomes for the entity; (iii) strategies for the management of the credit union are reflected in initiatives that aggregate and involve all employees through the methodology proposed by the BSC.